Primary health-care costs associated with special health care needs up to age 7 years: Australian population-based study - Quach, J; Oberklaid, F; Wake, M; Lucas, N; Mensah, F; Gold, L (My University, 2014)
AIM: We studied infants and children with and without special health care needs (SHCN) during the first 8 years of life to compare the (i) types and costs to the government's Medicare system of non-hospital health-care services and prescription medication in each year and (ii) cumulative costs according to persistence of SHCN. METHODS: Data from the first two biennial waves of the nationally representative Longitudinal Study of Australian Children, comprising two independent cohorts recruited in 2004, at ages 0-1 (n = 5107) and 4-5 (n = 4983) years. Exposure condition: parent-reported Children with Special Health Care Needs Screener at both waves, spanning ages 0-7 years. OUTCOME MEASURE: Federal Government Medicare expenditure, via data linkage to the Medicare database, on non-hospital health-care attendances and prescriptions from birth to 8 years. RESULTS: At both waves and in both cohorts, >92% of children had complete SHCN and Medicare data. The proportion of children with SHCN increased from 6.1% at age 0-1 years to 15.0% at age 6-7 years. Their additional Medicare costs ranged from $491 per child at 6-7 years to $1202 at 0-1 year. This equates to an additional $161.8 million annual cost or 0.8% of federal funding for non-hospital-based health care. In both cohorts, costs were highest for children with persistent SHCNs. CONCLUSIONS: SHCNs incur substantial non-hospital costs to Medicare, and no doubt other sources of care, from early childhood. This suggests that economic evaluations of early prevention and intervention services for SHCNs should consider impacts on not only the child and family but also the health-care system.
Journal of Paediatrics and Child Health
Keywords: Children -- Infants; Children; Health -- Access to services; Child Development; Childhood and child development; Health and wellbeing; Child Development; Health; Children; Infants; Access to services; Childhood and child development; Health and wellbeing